Influence of a hard transition layer on the microstructure and properties of diamond-like carbon/hydroxyapatite composite coating prepared by magnetron sputtering. Issue 6 (June 2021) - Qi, Jianwei; Xu, Fengkai; Bao, Kang; Li, Peixuan; He, Danfeng; Chen, Kai; Wang, Qingliang
Highlights: Gradient nanostructured DLC/HA multi-layer coating fabricated on Ti-6Al-4 V substrate by RF-magnetron sputter was firstly reported. DLC transition interlayer enhanced the nanohardness (10.4 GPa), adhesion strength (26.5 N) and corrosion resistance (icorr, 6.34 × 10 −9 A·cm -2 ; Ecorr, −46 mV) of DLC/HA coating. Compared with single-layer HA, the dense DLC transition layer can reduce the release of harmful metal ions by more than 20 %. Surface HA layer soaking in SBF solution can induce in situ generation of bone-like apatite. Abstract: The nanostructured diamond-like carbon/hydroxyapatite composite coating (DLC/HA) was deposited using magnetron sputtering technique with a densely packed columnar cross-sectional structure and a uniform granular surface morphology. After heat treatment, the amorphous structure of the coating was transformed into a crystal structure. Nanohardness and scratch tests results demonstrated the DLC transition layer significantly enhanced the nanohardness of Ti6Al4V substrates from 4.8 GPa to 10.4 GPa, and increased critical load from 16.6 N (pure HA layer) to 26.5 N (DLC layer) without obvious brittle fracture, flaking and delamination. Electrochemical and immersion tests results demonstrated that DLC/HA composite coatings with a dense gradient transition interlayer had better corrosion resistance and could prevent harmful metal ions being released into the SBF solution more effectively than single HA coatings. Furthermore, active Ca 2+ ions can be rapidly released from the coating surface during initial immersion in the SBF solution, and facilitated the formation of bone-like apatite.